Colossal permittivity and low losses in Ba1–xSrxTiO3–δ reduced nanoceramics. Issue 3 (February 2016) - Dupuis, Sébastien; Sulekar, Soumitra; Kim, Ji Hyun; Han, Hyuksu; Dufour, Pascal; Tenailleau, Christophe; Nino, Juan Claudio; Guillemet-Fritsch, Sophie
Abstract: The oxalate route offers a controlled approach to synthesize pure Ba1– x Sr x TiO3 (BST) (0 ≤  x  ≤ 1) nanoparticles ( ϕ  ≈ 150 nm in diameter). Reduced BST dense nanoceramics were obtained by spark plasma sintering (SPS) and then annealed for a short time to reach colossal permittivity ( ϵ ′ r  = 10 5 ) with low dielectric losses (tan δ  = 0.03) at 1 kHz and 300 K. The effects of Ba–Sr substitution on structural, microstructural and electrical properties were analyzed. Comprehensive analysis of the electrical properties indicates that polaron hopping, mediated by Ti 3+ ions and oxygen vacancies is the main contributing mechanism to colossal permittivity in Ba-rich BST compounds. Substitution of Ba by Sr reduced the contribution of polaron hopping and led to a decrease of real and imaginary parts of permittivity, while preserving interfacial polarization and yielding better temperature stability. The lowest temperature coefficient of capacitance, or TCC (variation of capacitance between 310 K and 450 K) value, i.e., 44 ppm K −1, is obtained for SrTiO3 .